2018
DOI: 10.3847/1538-4357/aae68a
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Filaments, Polarity Inversion Lines, and Coronal Hole Properties with the Sunspot Cycle: An Analysis of the McIntosh Database

Abstract: Filaments and coronal holes, two principal features observed in the solar corona are sources of space weather variations. Filament formation is closely associated with polarity inversion lines (PIL) on the solar photosphere which separate positive and negative polarities of the surface magnetic field. The origin of coronal holes is governed by largescale unipolar magnetic patches on the photosphere from where open magnetic field lines extend to the heliosphere. We study properties of filaments, PILs and corona… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 45 publications
14
33
0
Order By: Relevance
“…A bimodal nature in latitudinal distribution of filaments is observed (Hao et al, 2015;Mazumder et al, 2018). Tlatov et al (2016), Chatterjee et al (2017), Hao et al (2015), and Mazumder et al (2018) have reported a butterfly structure in the temporal variation of the latitudinal distribution of filaments. The butterfly diagram is similar to that of sunspot except that the spread in latitude is broader in case of filaments.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…A bimodal nature in latitudinal distribution of filaments is observed (Hao et al, 2015;Mazumder et al, 2018). Tlatov et al (2016), Chatterjee et al (2017), Hao et al (2015), and Mazumder et al (2018) have reported a butterfly structure in the temporal variation of the latitudinal distribution of filaments. The butterfly diagram is similar to that of sunspot except that the spread in latitude is broader in case of filaments.…”
Section: Introductionmentioning
confidence: 98%
“…The variation of filament number is found to be cyclic in close proximity to sunspot number variation (Hao et al, 2015;Li et al, 2010). The total filament length in the Carrington map is also found to vary cyclically with time (Tlatov et al, 2016;Mazumder et al, 2018). Mazumder et al (2018) further classified the filaments as associated and unassociated to solar activity belt according to their position inside or outside the sunspot activity belt respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2. The differential rotation effect could in addition explain the north-south symmetry and oblique orientation of the long-axis directions of a prominence, as observed and depicted by Mazumder et al (2018) in their Fig. 6, even if the long-axis direction of the prominence coincides with the direction of the photospheric neutral line, which is not the direction of the distorted north-south magnetic field.…”
Section: Discussionmentioning
confidence: 69%